Women Have It Easier : Estimating Gender Disparities in Criminal Justice in the Czech Republic - Marková, Tereza; Dušek, Libor; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This thesis examines the effect of gender on the outcomes of criminal processes in the Czech Republic using the full universe of criminal cases from 1995 to 2015. Results based on linear probability models indicate that female defendants face a lower probability of charge by the state prosecutor, a lower probability of imprisonment and shorter prison terms than their male counterparts. On the other hand, women are more likely to be convicted at trial. Legal factors account for about a third of the gender differences, but even after controlling for extra-legal characteristics, a substantial gap in sentencing outcomes remains. The effect of gender on sentencing substantially varies across crime types, but not in a consistent way. The sentencing gender gap narrows over time for the probability of unconditional imprisonment for the length of sentence.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses